Discarding Relics of the Past: Patriation of Laws in the South Pacific - Corrin, Jennifer (Victoria University of Wellington Law Review, 2008)
Drawing on Professor Angelo’s work in relation to the patriation of law in Niue and Tokelau as an exemplar of best possible practice, Associate Professor Corrin argues in this article that the time has come for other small island jurisdictions to complete their own promised patriation projects. In her article Dr Corrin reviews the issues facing former British dependencies in assessing whether English law applies in their jurisdiction. Dr Corrin concludes that the situation is problematic and that the interests of the rule of law would be better fulfilled by the introduction or the completion of patriation programmes. She reviews case law from a wide range of former dependencies which demonstrate the complexities of applying the reception rule and that of the confusion that can result.